2013
DOI: 10.1248/bpb.b12-00902
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Reduces <i>SULT1E1</i> Expression in Human Colon Carcinoma Caco-2 Cells

Abstract: Recent epidemiological studies have shown that moderate coffee consumption is associated with a lower risk of certain types of cancers, particularly colon cancer in postmenopausal women. To elucidate the molecular basis for the preventive action of coffee, we investigated the effect of coffee on estrogen sulfotransferase (SULT) because sulfation is the major pathway involved in the inactivation of estrogens. We found that coffee reduced SULT1E1 gene expression in human colon carcinoma Caco-2 cells. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In vitro studies found that coffee reduced the phase II enzyme, estrogen sulfotransferases (SULT1E1) gene expression in Caco‐2 cells. Because sulfation is the major pathway involved in the inactivation of estrogens, the effect on SULT1E1 may enhance estrogen activity and thereby explain why the inverse association between coffee and cancer risk is more evident among subgroups of postmenopausal women for some cancers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies found that coffee reduced the phase II enzyme, estrogen sulfotransferases (SULT1E1) gene expression in Caco‐2 cells. Because sulfation is the major pathway involved in the inactivation of estrogens, the effect on SULT1E1 may enhance estrogen activity and thereby explain why the inverse association between coffee and cancer risk is more evident among subgroups of postmenopausal women for some cancers …”
Section: Discussionmentioning
confidence: 99%
“…Because sulfation is the major pathway involved in the inactivation of estrogens, the effect on SULT1E1 may enhance estrogen activity and thereby explain why the inverse association between coffee and cancer risk is more evident among subgroups of postmenopausal women for some cancers. 29 A number of epidemiologic studies have estimated the association between coffee consumption and the risk of breast cancer, but the results were inconclusive. Several case- 1 One cup of coffee 5 150 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that coffee consumption had the chemopreventive effect in colorectal cancer, and several bioactive compounds showed the pharmacological effectiveness ( Vitaglione et al ., 2012 ; Isshiki et al ., 2013 ). The present study demonstrated that kahweol, the coffee deterpene, significantly suppressed the viability of HT-29 human colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies found that coffee reduced the phase II enzyme, estrogen sulfotransferases (SULT1E1) gene expression in Caco‐2 cells with 60%. Because sulfation is the major pathway involved in the inactivation of estrogens, the effect on SULTE1 may enhance estrogen activity and thereby explain why the inverse association between coffee and cancer risk is more evident among subgroups of postmenopausal women for some cancers . The responsible bioactive constituents for the SULTE inhibition were produced under the roasting process.…”
Section: Possible Mechanisms For Chemoprevention By Coffeementioning
confidence: 99%